2017
DOI: 10.1002/pbc.26828
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profile and nutritional quality of a regular diet compared to a neutropenic diet in a pediatric oncology unit

Abstract: It has been hypothesized that a neutropenic diet has lower microbe content. Here, the microbiological and nutritional contents of regular and neutropenic diets offered to pediatric patients were analyzed. Microbiological contamination was detected in five of 36 of the food samples analyzed, yet there was no statistical differences between the diets (P = 1.00) or in their odds ratio (0.62) (95% CI = 0.05-6.35; P = 0.63). The strict neutropenic diet did have less fiber (P = 0.05) and vitamin C (P = 0.01). Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Given that ND does not show a lower microbiological burden and implements various dietary constraints, it results in low nutritional quality, compared to the consumption of a regular diet prepared with good hygiene care in pediatric cancer cases (20). There is little and limited evidence about the benefit of the use of an ND for newly diagnosed acute leukemia (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ND does not show a lower microbiological burden and implements various dietary constraints, it results in low nutritional quality, compared to the consumption of a regular diet prepared with good hygiene care in pediatric cancer cases (20). There is little and limited evidence about the benefit of the use of an ND for newly diagnosed acute leukemia (21).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional pattern of the hard ND was found to be lower in vitamin C as well as fiber compared to the regular diet, thereby it is thought to be symbolizing low nutritional insufficiency like fresh fruits as well as vegetables that are limited in ND (20). The cooking methods may also trigger nutritional deficiencies and a diet with poor nutritional quality (20). Vitamin C (ascorbic acid), with its significant characteristics as an antioxidant, is one of the most degraded nutrients in cooked fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of infection has been addressed by reducing the chance of acquiring an infection and by using prophylactic antibacterial therapy. Systematic reviews of the use of specialized “low-bacterial diets” to decrease the risk of bacterial translocation across the gut wall have demonstrated little benefit for this approach 1 , which is confirmed in a specific comparative study in children 2 . These diets are harder to adhere to for families, contain far less joy, and are convincingly unhelpful.…”
Section: Preventing Infectionmentioning
confidence: 95%
“…13 Most importantly, clinical trials have not found this diet to be effective in the prevention of infection over and above that of food safety guidelines. [13][14][15] It is plausible that incorporating foods and supplements high in pre-or probiotics may be safe and beneficial within the context of childhood cancer; however, additional research is needed. It is essential that dietary counseling within integrative oncology adheres to food safety guidelines to reduce the risk of food-borne illnesses.…”
Section: Neutropenic Diet/low Microbial Dietmentioning
confidence: 99%